World Bank Technical Assistance: The Relational Dynamics of Policy Movement. (24th February 2017) - Bazbauers, Adrian Robert
Summary: The World Bank has been widely critiqued as a global governance actor capable of coercing and persuading its developing member countries to accept its policy recommendations. This article contributes to academic discussion by drawing upon the policy transfer and policy mobilities literatures to analyse the World Bank's two main pillars of technical assistance (TA): TA components (advisory services contained within lending operations) and stand‐alone TA projects (loans and credits that solely finance TA). Beginning from the constructivist position that 'development' is a social construct, the article argues that relational dynamics between TA provider and recipient affect the perception of the legitimacy of policy norms transferred from the 'international' to the 'domestic'. The value added of the article is thus that policy legitimacy is not simply conferred by whether advice is technically sound but moreover through the social and political interactions—the relationship—between TA provider and recipient. Copyright © 2017 John Wiley & Sons, Ltd.